Next-generation shopping cart design based on design methods for consumer behaviour analysis - Hung, Yu Ching; Lee, Yann Long; Kiat, An Ting; Wong, Ann Yee; Chia, Mei See; Cai, Jhong Yan (2023)
A shopping cart is a very important aid to help customers to transport their goods in the market and mall. Sometimes there will be insufficient for a shopping cart in the supermarket. And the shopping carts are always scattered around everywhere inside or outside supermarkets. Based on this, researchers found out most of the people faced difficulty controlling the shopping cart and used a bad condition of the shopping cart before. Besides, customers have also faced problems of lack of information on promotions, inconvenient payment processes, and do not clear about the product location. Most people also faced problems during the payment process as they required to queue for a long time. According to the statements above, the problems that can ruin customers’ shopping experiences are the bad condition of a shopping cart, insufficient shopping cart, current payment method with low efficiency, and lack of information about product location and promotion. In this research, the project target to aim for the design 2040. Here use several design methods, such as product specification analysis, market positioning analysis, Morphological analysis, and KJ (Kawakita Jiro) method to define the market objective and problem-solving. Designers are going to design a product which is a smart shopping trolley that can benefit human life in 2040. Besides, this shopping cart was designed able to enhance the customers’ shopping experiences and improve the shopping process by solving all the problems faced by customers. In conclusion, researchers achieve the objectives stated to design a future product that able to enhance the shopping experience in 2040 which is a smart shopping cart by using the design tools and industrial design principles.